Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/14651858.cd001150.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Topical emollient for preventing infection in preterm infants

Abstract: Editorial group: Cochrane Neonatal Group. Publication status and date: New search for studies and content updated (conclusions changed), published in Issue 5, 2021.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…Alternatively, natural oils have been in longstanding traditional use, but some oils may be harmful ( 104 , 105 ) while others have advantages with particular fatty acid profiles (e.g., higher linoleic acid content) ( 106 – 108 ). The use of sunflower oil as an emollient demonstrated a reduction in infections in neonates in a hospital-based study ( 109 ), and encouraging trends in a subgroup analysis of very low birth weight infants in a community-based study ( 106 ); however, more evidence is required ( 110 ). The strategy of combining emollients with antiseptics has also been the subject of recent pilot studies ( 47 ) and warrants further research.…”
Section: Maintenance Of Skin Integritymentioning
confidence: 99%
“…Alternatively, natural oils have been in longstanding traditional use, but some oils may be harmful ( 104 , 105 ) while others have advantages with particular fatty acid profiles (e.g., higher linoleic acid content) ( 106 – 108 ). The use of sunflower oil as an emollient demonstrated a reduction in infections in neonates in a hospital-based study ( 109 ), and encouraging trends in a subgroup analysis of very low birth weight infants in a community-based study ( 106 ); however, more evidence is required ( 110 ). The strategy of combining emollients with antiseptics has also been the subject of recent pilot studies ( 47 ) and warrants further research.…”
Section: Maintenance Of Skin Integritymentioning
confidence: 99%
“…In this scenario, a preventive role of the policies of any single center regarding other prevention strategies can not be excluded. In neonates, fluconazole is generally well tolerated [ 28 , 29 , 30 ], but some concerns on the possible risk of neurodevelopmental impairment have been raised in the past [ 31 , 32 ]. Anyway, no negative effects in neonates under 750 g evaluated at 18 to 22 months of corrected age have been documented [ 20 ], and the evaluation at 8 to 10 years of life of neurodevelopmental status and quality of life of survivors from a randomized, placebo-controlled trial of fluconazole prophylaxis showed no differences in quality of life, behavior, communication, motor skills, and school performance [ 33 ].…”
Section: Pharmacological Prophylaxis With Antifungal Drugsmentioning
confidence: 99%
“…Applications of some moisturisers, such as Aquaphor and Eucerin, have been shown to enhance skin barrier function, but not clinical outcomes in preterm neonates [ 13 ]. In contrast, several studies in cohorts of preterm infants in low-and middle-income countries have shown that sunflower seed oil (SSO) with high linoleic acid content (eg, >60%) provides benefits for the skin barrier and the survival, health, growth, and development of newborn infants [ 14 - 17 ].…”
Section: Use Of Emollients To Improve Skin Barrier Function and Healthmentioning
confidence: 99%